Resource and Human Capital Synergies as Determinants of MSME Growth: Evidence from Bislig City, Philippines - Calub, Floresito Dumagan (International Review of Management and Marketing, 2026)
Micro, Small, and Medium Enterprises (MSMEs) fuel local innovation and employment but continue to face growth constraints in emerging economies. This study examined how internal firm characteristics enterprise size, years of operation, and owner’s educational attainment influence MSME performance in Bislig City, Philippines. Drawing on the Resource-Based View and Human Capital Theory, the research employed a quantitative correlational design using survey data from 236 MSME owners and managers. Multiple regression analysis revealed that enterprise size exerted the strongest influence on both sales’ growth and profitability, followed by years of operation and educational attainment. The results confirmed that firm performance depends on how entrepreneurs mobilize resources and apply managerial competence to overcome market limitations. By situating the analysis in a small urban economy in Mindanao, the study extended existing theories to a new context and provided empirical evidence for localized MSME policy design. The findings highlight the need for education-driven capacity building, innovation training, and credit access programs to strengthen MSME resilience and contribution to Sustainable Development Goals 8 and 9.